Corruption Cases In Banking Practices - Farah Putri Firsanty (Universitas Padjadjaran, 2018)
ABSTRACT This paper focus on corruption cases in banking practices. Social control is a well-planned process or not that is educational, invite, and even force all citizens to comply with the prevailing social norms. By nature, social control by nature is divided into two namely preventive and repressive. Preventive, is a social control performed to prevent events that have not occurred or is an attempt made before the occurrence of a violation. In a public preventive or a person is directed, persuaded, or reminded not to commit the offense mentioned. Furthermore, it is repressive, constituting a social control performed after the occurrence of an offense or is an attempt made after the offense occurred. This research is using qualitative methods and used primary data: participatory observation and in-depth interviews. Finally, research findings concluded that banking industry both BUMN and private have preventive and repressive efforts in minimizing corruption cases in banking practices. Started from the internal bank itself and then continued by external agencies namely Bank of Indonesia (BI) and the Financial Services Authority (OJK). Furthermore, if a banker has been declared to violate the Bank of Indonesia Circular Letter and / or OJK Regulation then it will be processed by the institution or the authorized party namely Police. Especially for corruption cases in the banking practices of a Bank which is a State-Owned Enterprise (BUMN), a banker who is a suspect in a corruption case can be investigated by Indonesia’s Corruption Commission (KPK) because BUMN is state-owned bank.